Preparation method of multistage micro-nano structure composite material for nuclear radiation detection
By preparing multi-stage micro-nano structural composite materials, the simultaneous detection of neutrons and gamma rays is achieved using SERS and LSPR spectroscopy technology, the problem of difficulty in distinguishing radiation types in the radiation field environment in the prior art is solved, and the accuracy and stability of the detection are improved.
Patent Information
- Application Number
- CN202510320889.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-18
- Publication Date
- 2025-07-25
- Estimated Expiration
- 2045-03-18
AI Technical Summary
Existing nuclear radiation detection materials are difficult to accurately distinguish and measure different types of nuclear radiation in complex radiation field environments, resulting in difficulty in measuring mixed radiation field doses.
Multi-stage micro-nano structural composite materials are used to prepare functionalized nano-gold cores, nano-gold shells and nano-silver shells with boron-containing molecules through gold-sulfur self-assembly technology, which are used for neutron and gamma ray detection respectively, and quantitative measurement of signals is achieved using SERS and LSPR spectra.
It realizes rapid and accurate detection of neutrons and gamma rays, improves the uniformity and stability of radiation response, simplifies the signal reading process, and reduces device dependence.
Smart Images

Figure CN120362505A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nuclear radiation detection, and in particular to a method for preparing a multi-level micro-nano structure composite material for nuclear radiation detection. Background Art
[0002] With the rapid development of the nuclear energy and nuclear technology industries, nuclear radiation detection technology has generated urgent needs in multiple application fields. In practical applications such as radiotherapy, radiation processing, and radiation effect research, accurate radiation dose delivery is crucial to ensuring the reliability of radiation practice activities. In nuclear emergency situations, rapid and accurate dose measurement is not only the key basis for assessing the degree of radiation damage to the exposed population, but also an important reference for the classification and disposal of medical rescue. Therefore, the development of advanced nuclear radiation detection technology and high-performance radiation detection materials to achieve rapid and accurate measurement of complex nuclear radiation fields has important application value.
[0003] Thermoluminescent materials, photoluminescent materials, radiation photoluminescent materials, radiation-induced chromic materials and gel materials have played an important role in the field of nuclear radiation detection. Due to their unique physical and chemical properties, they can produce specific responses to nuclear radiation and are then used in radiation dose measurement. In recent years, in order to further improve the sensitivity of radiation detection, researchers have developed new detection materials such as quantum dots, carbon nanomaterials, boron-based nanomaterials, perovskites and metal-organic framework materials. Studies have shown that by regulating the composition and structure of the detection material, its radiation response characteristics (such as sensitivity, linearity, response range, etc.) can be effectively adjusted to meet the diverse needs of radiation detection in different application scenarios. However, limited by the detection principle and signal readout method, the existing detection materials face the problem of mutual interference when applied to complex radiation field environments. Different types of radiation may have complex and comprehensive effects on the material, making it difficult to accurately distinguish and measure various radiation doses in mixed radiation fields. Therefore, how to quickly and accurately detect different types of nuclear radiation in a single type of material at the same time has become a technical problem that needs to be solved in this field. Summary of the invention
[0004] Aiming at the above technical problems, the purpose of the present invention is to provide a multi-level micro-nano structure composite material for nuclear radiation detection and its preparation method. The composite material is prepared by gold-sulfur self-assembly technology and seed growth method, and has a multi-level micro-nano structure with gold nanoparticles as the core, boron-containing molecules as the neutron detection medium, gold nanoshells as the surface-enhanced Raman scattering carrier, and silver nanoshells as the gamma-ray detection medium; the neutron response of the boron-containing molecules is derived from the nuclear reaction between boron-10 and neutrons, resulting in changes in the molecular structure, which is quantitatively and sensitively characterized by SERS spectra; the gamma-ray response of the silver nanoshells is derived from the free radical-mediated oxidation etching effect caused by gamma radiation, which is quantitatively and sensitively characterized by LSPR spectra; through SERS / LSPR dual-channel measurement, the simultaneous, rapid and accurate detection of neutron-gamma mixed radiation fields can be achieved.
[0005] Specifically, the above object of the invention is achieved by the following technical solutions:
[0006] First, the present application provides a preparation method of a multi-level micro-nano structure composite material for nuclear radiation detection, including the following steps:
[0007] 1) Preparation of boron-containing molecule-functionalized gold nanocores
[0008] Add the boron-containing molecule solution to the gold nanoparticle solution coated with surfactant I, and stir and react at room temperature for 4-8 h under a nitrogen atmosphere; centrifuge the reaction solution and discard the supernatant to remove unreacted boron-containing molecules; redisperse the precipitate in the surfactant II solution to obtain a boron-containing molecule-functionalized gold nanocore solution for standby;
[0009] The surfactant I in the above gold nanoparticle solution coated with surfactant I is the same as surfactant II.
[0010] 2) Preparation of functionalized gold nanocore-gold nanoshells
[0011] Add chloroauric acid solution and ascorbic acid solution to the surfactant III solution in sequence, and vortex and oscillate for 3 min to mix them quickly and evenly to obtain a mixed solution A; add the boron-containing molecule-functionalized gold nanocore solution obtained in step 1) to the mixed solution A, and stir and react at 40 °C for 1-3 h until the solution color no longer changes, stop heating, and continue to stir for 1 h after the solution cools to room temperature; centrifuge the reaction solution and discard the supernatant to remove unreacted reagents; resuspend the precipitate in ultrapure water to obtain functionalized gold nanocore-gold nanoshells with a particle size of about 22-65 nm.
[0012] 3) Preparation of functionalized gold nanocore-gold nanoshell-silver nanoshells
[0013] Under stirring conditions, add the functionalized gold nanocore-gold nanoshell solution obtained in step 2) to the silver nitrate solution, then add the ascorbic acid solution dropwise, and use 0.1 M sodium hydroxide solution to adjust the pH of the reaction system to 7-9 to promote the uniform deposition of silver nanoshells. Stir and react at 50 °C for 1-3 h until the solution color no longer changes, stop heating, and continue to stir for 1 h after the solution cools to room temperature; centrifuge the reaction solution and discard the supernatant to remove unreacted reagents; resuspend the precipitate in ultrapure water to obtain functionalized gold nanocore-gold nanoshell-silver nanoshell, which is a multi-level micro-nano structured composite material for nuclear radiation detection, and its particle size ranges from 25 to 70 nm.
[0014] Preferably, in the above step 1), the boron-containing molecule contains a mercapto group and a benzene ring, preferably 4-mercaptobenzeneboronic acid pinacol ester, mercaptobenzeneboronic acid or its derivatives (complexes formed by mercaptobenzeneboronic acid and molecules with cis-diol structures, such as mercaptobenzeneboronic acid-fructose complex, mercaptobenzeneboronic acid-glucose complex, mercaptobenzeneboronic acid-sialic acid complex, etc.), and the solution concentration of the boron-containing molecule is preferably 0.1-2 mM; a gold-sulfur bond is formed between the gold nanoparticles and the mercapto group of the boron-containing molecule through self-assembly to achieve functionalization.
[0015] Preferably, the above surfactant I, surfactant II, and surfactant III are the same, and are one of cetyltrimethylammonium bromide, cetyltrimethylammonium chloride, or polyvinylpyrrolidone; the gold nanoparticles are spherical particles with a particle size of 20-60 nm, and their solution concentration is 0.1-1 μM; in terms of molar mass, the dosage ratio of the added boron-containing molecule to the gold nanoparticles is 200:1-500:1.
[0016] Preferably, in step 2), the type of surfactant is the same as that in step 1), and its concentration is 0.05-0.2 M; the concentration of chloroauric acid in the mixed solution A is 0.1-0.5 mM; the concentration of ascorbic acid in the mixed solution A is 0.6-3.0 mM; in terms of molar mass, ascorbic acid (C6H8O6): chloroauric acid: boron-containing molecule-functionalized gold nanocore = 12:2:1.
[0017] Preferably, in step 3), the concentration of the silver nitrate solution is 10-20 mM; the concentration of the ascorbic acid solution is 40-80 mM; in terms of molar mass, the added ascorbic acid: silver nitrate: functionalized gold nanocore-gold nanoshell = 8:2:1; in this step, the added ascorbic acid affects the deposition rate and deposition uniformity of the silver nanoshells in the final product, the dosage of silver nitrate affects the thickness of the silver nanoshells, and the dosage of each component ultimately affects the radiation response sensitivity. The finally obtained functionalized gold nanocore-gold nanoshell-silver nanoshell has a particle size of 25-70 nm.
[0018] Secondly, the present application provides a multi-level micro-nano structured composite material for nuclear radiation detection prepared according to the above method. From the inside out, the composite material consists of multi-level micro-nano structures such as a nano-gold core, boron-containing molecules, a nano-gold shell, and a nano-silver shell; the boron-containing molecules between the nano-gold core and the nano-gold shell are used to detect neutrons, and the enhanced electromagnetic field in the nano-gold core-nano-gold shell gap can excite the surface-enhanced Raman scattering (SERS) effect. The response of the boron-containing molecules to neutrons is quantitatively measured through the SERS spectrum; the nano-silver shell with the local surface plasmon resonance (LSPR) effect is used to detect gamma radiation, and the response of the nano-silver shell to gamma radiation is quantitatively measured through the LSPR spectrum.
[0019] Compared with the prior art, the method for preparing the multi-level micro-nano structured composite material and the material provided by the present application have the following beneficial effects:
[0020] (1) The preparation method has simple steps and does not involve harsh conditions required for solid-phase synthesis, hydrothermal synthesis, etc., which is convenient for implementation;
[0021] (2) The neutron detection material (boron-containing molecules) and gamma-ray detection material (nano-silver shell) prepared by this method are integrated into the multi-level micro-nano structure, enabling simultaneous detection of neutrons and gamma rays;
[0022] (3) The neutron detection material prepared by this method is located in the nano-gold core-nano-gold shell gap and is physically isolated from the gamma-ray detection material, which is beneficial to improving the uniformity and stability of radiation response;
[0023] (4) The readout method of the neutron detection material prepared by this method is simple. The measurement means of the neutron response signal is the SERS spectrum, and the measurement means of the gamma-ray response signal is the LSPR spectrum. Direct readout is achieved and there is no crosstalk between the two, enabling efficient discrimination of the dose in the mixed radiation field and solving the problem that the signal readout of existing scintillator materials, etc., requires a scintillation detector and a supporting spectrometer, which has a large dependence on equipment. Description of the Drawings
[0024] Figure 1 It is a flowchart of the preparation method of the multi-level micro-nano structured composite material for nuclear radiation detection in the embodiment.
[0025] Figure 2 It is a TEM image of the boron-containing molecule-functionalized nano-gold core prepared in the embodiment.
[0026] Figure 3 It is a TEM image of the functionalized nano-gold core-nano-gold shell prepared in the embodiment.
[0027] Figure 4 It is a schematic structural diagram of the multi-level micro-nano structured composite material for nuclear radiation detection;
[0028] Among them, 1 - gold nanocore, 2 - boron - containing molecule, 3 - gold nanoshell, 4 - silver nanoshell.
[0029] Figure 5 TEM image of the functionalized gold nanocore - gold nanoshell - silver nanoshell prepared in the example.
[0030] Figure 6 SERS spectrum of the multi - level micro - nano structure composite material prepared in the example. Detailed implementation manners
[0031] The following combines the drawings and examples to clearly and completely describe the technical solutions of the present invention. Obviously, the described examples are only a part of the examples of the present invention, rather than all the examples. Based on the examples in the present invention, all other examples obtained by those of ordinary skill in the art without creative efforts shall fall within the protection scope of the present invention.
[0032] The instruments and reagents involved in the following examples are obtained through commercial channels unless otherwise specified.
[0033] The solution of spherical gold nanoparticles coated with cetyltrimethylammonium bromide is purchased from Suzhou Beike Nano - Technology Co., Ltd.
[0034] Example 1
[0035] In this example, the flowchart of the preparation method of the multi - level micro - nano structure composite material for nuclear radiation detection is as Figure 1 shown, and the specific steps are as follows:
[0036] 1) Preparation of boron - containing molecule - functionalized gold nanocore
[0037] Add the solution of 4 - mercaptophenylboronic acid pinacol ester (1 mM) to the solution of spherical gold nanoparticles coated with cetyltrimethylammonium bromide (the particle size of the nanoparticles is 30 nm, 0.5 μM). The molar ratio of the added 4 - mercaptophenylboronic acid pinacol ester to the gold nanoparticles is 200:1;
[0038] Under a nitrogen atmosphere, stir - react at room temperature for 8 h; centrifuge the reaction solution (10,000 rpm, 20 min), discard the supernatant to remove the unreacted 4 - mercaptophenylboronic acid pinacol ester; redisperse the precipitate in the cetyltrimethylammonium bromide solution (0.1 M) to obtain a 4 - mercaptophenylboronic acid pinacol ester - functionalized gold nanocore solution (concentration is 2 μM), which is the boron - containing molecule - functionalized gold nanocore and is reserved; the TEM image of the boron - containing molecule - functionalized gold nanocore prepared in this step is as Figure 2 shown.
[0039] 2) Preparation of functionalized gold nanocore - gold nanoshell
[0040] To a cetyltrimethylammonium bromide solution (0.1 M), chloroauric acid solution (5 mM) and ascorbic acid solution (30 mM) were successively added, and vortexed for 3 min to mix them evenly quickly, obtaining a mixed solution A (the final concentration of chloroauric acid in the mixed solution A was 0.5 mM; the final concentration of ascorbic acid in the mixed solution A was 3.0 mM).
[0041] The 4-mercaptobenzeneboronic acid pinacol ester-functionalized gold nanocore solution obtained in step 1) was added to the mixed solution A (in terms of molar mass, ascorbic acid: chloroauric acid: boron-containing molecule-functionalized gold nanocore = 12:2:1), and stirred at 40 °C for 2 h until the solution color no longer changed, then the heating was stopped. After the solution cooled to room temperature, it was stirred for another 1 h. The reaction solution was centrifuged (10,000 rpm, 20 min), and the supernatant was discarded to remove unreacted reagents. The precipitate was resuspended in ultrapure water to obtain functionalized gold nanocore-gold nanoshell (final concentration of 2 μM) for standby. The TEM image of the functionalized gold nanocore-gold nanoshell prepared in this step is as Figure 3 shown.
[0042] 3) Preparation of functionalized gold nanocore-gold nanoshell-silver nanoshell
[0043] Under stirring conditions, the functionalized gold nanocore-gold nanoshell solution obtained in step 2) was added to silver nitrate solution (10 mM), and then ascorbic acid solution (40 mM) was added dropwise, and the pH of the system was adjusted to 7-9 with 0.1 M sodium hydroxide solution to promote the uniform deposition of silver nanoshell (in terms of molar mass, ascorbic acid: silver nitrate: functionalized gold nanocore-gold nanoshell = 8:2:1). It was stirred at 50 °C for 2 h until the solution color no longer changed, then the heating was stopped. After the solution cooled to room temperature, it was stirred for another 1 h. The reaction solution was centrifuged (10,000 rpm, 20 min), and the supernatant was discarded to remove unreacted reagents. The precipitate was resuspended in ultrapure water to obtain a functionalized gold nanocore-gold nanoshell-silver nanoshell composite material.
[0044] The structural schematic diagram of this composite material is as Figure 4 shown. It can be seen that from the inside out, this composite material is composed of multi-level micro-nano structures such as gold nanocore 1, boron-containing molecule 2, gold nanoshell 3, and silver nanoshell 4.
[0045] The TEM image of this composite material is as Figure 5 shown. Figure 2 , Figure 3 , Figure 5TEM images of boron-containing molecule-functionalized gold nanocores, functionalized gold nanocore-gold nanoshells, and functionalized gold nanocore-gold nanoshell-silver nanoshells are shown respectively. Their micro-morphologies are all spherical, indicating that the gold nanocores are not affected during the step-by-step preparation process. The particle size of the gold nanocore-gold nanoshell is slightly increased compared with that of the boron-containing molecule-functionalized gold nanocore. A thin silver shell is clearly shown in the functionalized gold nanocore-gold nanoshell-silver nanoshell, indicating that the composite material has been successfully prepared.
[0046] According to the GB / T 40219-2021 standard, the SERS spectra of the obtained composite materials were tested using a Raman spectrometer (InVia, Renishaw), as Figure 6 shown. The SERS spectral peaks are sharp and have high intensity. The characteristic peaks of the boron-related functional groups near 1580 and 1570 cm -1 are clearly distinguishable, indicating that the SERS effect is effectively excited in the gap between the gold nanocore and the gold nanoshell and the gold nanocore is effectively functionalized by the boron-containing molecules. According to the GB / T 26810-2011 standard, the LSPR spectra of the obtained composite materials were tested using an ultraviolet-visible spectrophotometer (UV-2550, Shimadzu). It has an absorption peak near 550 nm and 400 nm respectively, which originate from the extinction characteristics of the gold nanostructure and the silver nanoshell.
[0047] The nuclear radiation detection performance of the obtained composite materials was tested using an Am-Be neutron source (moderated) and 60 a Co gamma-ray source. The specific process is as follows:
[0048] 1) The obtained composite materials were irradiated using an Am-Be neutron source (moderated) with a neutron dose of 1 - 50 mGy, and their SERS spectra were tested to evaluate their neutron response performance;
[0049] 2) The obtained composite materials were irradiated using 60 a Co gamma-ray source with a gamma dose of 4 Gy, and their SERS spectra were tested to evaluate their anti-gamma-ray interference performance;
[0050] 3) The obtained composite materials were irradiated using 60 a Co gamma-ray source with a gamma dose of 1 - 10 Gy, and their LSPR spectra were tested to evaluate their gamma-ray response performance;
[0051] 4) The obtained composite materials were irradiated using an Am-Be neutron source (moderated) with a neutron dose of 200 mGy, and their LSPR spectra were tested to evaluate their anti-neutron interference performance.
[0052] The test results show that: the SERS spectra of the obtained composite materials have a good response to the neutron dose. Using 1570 and 1580 cm -1The relative intensities of two characteristic peaks are fitted to the neutron dose, and the equation is y = 8.126x + 0.141 (R 2 = 0.972). The signal drift caused by gamma-ray irradiation is about 1.6%, indicating good anti-gamma-ray interference performance; the LSPR spectrum has a good response to gamma-ray dose. The relative intensities of the absorption peaks at 550 and 400 nm are fitted to the gamma-ray dose, and the equation is y = 0.218x + 0.512 (R 2 = 0.983). The signal drift caused by neutron irradiation is about 0.9%. In summary, the obtained multi-level micro-nano structure composite material can be used for nuclear radiation detection and can distinguish the dose of the mixed radiation field.
Claims
1. A preparation method of a multi-level micro-nano structure composite material for nuclear radiation detection, characterized in that, The specific steps are as follows: 1) Add the boron-containing molecular solution to the gold nanoparticle solution coated with surfactant I, and stir and react under a nitrogen atmosphere; then centrifuge, take the precipitate and disperse it in surfactant II to obtain a boron-containing molecular-functionalized nano-gold core solution for standby; The boron-containing molecule is at least one of 4-mercaptobenzeneboronic acid pinacol ester, mercaptobenzeneboronic acid or mercaptobenzeneboronic acid derivative; the mercaptobenzeneboronic acid derivative is a complex formed by mercaptobenzeneboronic acid and a molecule containing a cis-diol structure; 2) Sequentially add chloroauric acid and ascorbic acid solution I to surfactant III to obtain a mixed solution for standby; Add the boron-containing molecular-functionalized nano-gold core solution obtained in step 1) to the mixed solution, stir and react until the solution color no longer changes. After the solution is cooled to room temperature, centrifuge, and resuspend the precipitate in ultrapure water to obtain a functionalized nano-gold core-nano-gold shell solution; 3) Under stirring conditions, add the functionalized nano-gold core-nano-gold shell solution obtained in step 2) to a silver nitrate solution, and then dropwise add ascorbic acid II, adjust the pH to 7-9, stir and react until the solution color no longer changes. After the solution is cooled to room temperature, centrifuge, and the precipitate obtained is the multi-level micro-nano structure composite material for nuclear radiation detection; Surfactant I, surfactant II, and surfactant III are of the same type, and are one of cetyltrimethylammonium bromide, cetyltrimethylammonium chloride or polyvinylpyrrolidone.
2. The preparation method of the multi-stage micro-nano structure composite material for nuclear radiation detection according to claim 1, characterized in that, In step 1), the concentration of the boron-containing molecular solution is 0.1-2 mM.
3. The preparation method of the multi-level micro-nano structure composite material for nuclear radiation detection according to claim 1, characterized in that In step 1), the particle size of the gold nanoparticles coated with surfactant I is 20-60 nm, and the concentration of its solution is 0.1-1 μM.
4. The preparation method of the multi-stage micro-nano structure composite material for nuclear radiation detection according to claim 1, characterized in that, In step 1), the molar mass ratio of the added boron-containing molecule to the gold nanoparticles coated with surfactant I is 200:1-500:
1.
5. The preparation method of the multi-stage micro-nano structure composite material for nuclear radiation detection according to claim 1, characterized in that, The concentrations of surfactant I, surfactant II, and surfactant III are all 0.05-0.2 M.
6. The preparation method of the multi-level micro-nano structure composite material for nuclear radiation detection according to claim 1, characterized in that, In the mixed solution in step 2), the molar concentration of chloroauric acid is 0.1-0.5 mM, and the molar concentration of ascorbic acid I is 0.6-3.0 mM.
7. The preparation method of the multi-level micro-nano structure composite material for nuclear radiation detection according to claim 1, characterized in that, In step 2), the molar ratio of ascorbic acid I, chloroauric acid, and boron-containing molecular-functionalized nano-gold core is 12:2:
1.
8. The preparation method of the multi-level micro-nano structure composite material for nuclear radiation detection according to claim 1, characterized in that, In step 3), the molar concentration of the silver nitrate solution is 10-20 mM; the molar concentration of ascorbic acid II is 40-80 mM.
9. The preparation method of the multi-level micro-nano structure composite material for nuclear radiation detection according to claim 1, characterized in that, In step 3), the molar mass ratio of ascorbic acid II, silver nitrate, and functionalized nano-gold core-nano-gold shell is 8:2:1 in sequence.
10. A multi-level micro-nano structure composite material for nuclear radiation detection prepared by any of the methods as claimed in claims 1-9.
Citation Information
Patent Citations
SERS active substrate for detecting thermal neutron radiation, and preparation method and application thereof
CN107167834A
Gold nanostar @ gold-silver alloy Raman base material with high activity and preparation method thereof
CN109128152A
Gold-core silver-shell nanometer composite material and preparation method thereof
CN109596822A
Synthesis of oligonucleotide mediated gold core- silver shell nanoparticles
WO2010109268A1